Karakteristik Deiksis Tempat dan Waktu dalam Novel Indonesia Mutakhir: Studi pada Novel Karya Tere Liye - Fajri, Ahmad; Agustina, Agustina (Persona: Kajian Bahasa dan Sastra, 2024)
The objectives of this research are to (a) describe the types of spatial and temporal deixis found in the contemporary Indonesian novel by Tere Liye: Hujan dan Si Putih, and (b) describe the functions of each spatial and temporal deixis based on its usage context in the contemporary Indonesian novel by Tere Liye: Hujan dan Si Putih. This research is a qualitative study with a descriptive method. The data used are words, phrases, sentences, and utterances that contain deixis forms in the novel Hujan dan Si Putih by Tere Liye. The data collection technique used is the note-taking technique. The steps of data analysis in this research are: (1) reading and understanding the novel Hujan dan Si Putih by Tere Liye, (2) identifying each word and phrase that contains types of spatial and temporal deixis found in the novel Hujan dan Si Putih by Tere Liye, (3) classifying spatial and temporal deixis into a table that has been created based on its type, (4) analyzing data on the use of deixis found in the novel, and (5) reporting the results of the data in the form of a research report. The research findings are as follows. First, in the novel Hujan, there are 1,014 uses of spatial and temporal deixis, with details: spatial deixis as many as 710 data with a percentage of 70.19% and temporal deixis 306 data with a percentage of 29.81%. Meanwhile, in the novel Si Putih, there are 1,208 data with details: spatial deixis as many as 905 data with a percentage of 74.92% and temporal deixis as many as 303 data with a percentage of 25.08%. So the total number of uses of spatial and temporal deixis found in the novel Hujan dan Si Putih by Tere Liye is 2,222 data. Second, the function of the use of spatial deixis in the novel Hujan dan Si Putih by Tere Liye refers to the use of spatial pronouns, other names for a place, place nouns, and spatial prepositions. In temporal deixis, it refers to the use of time pronouns and place nouns.